Tourism Service Quality Affecting the Satisfaction of Foreign Tourists: A Case Study Of Ho Chi Minh City - Van Trai and Nguyen Thanh Van, Nguyen (British Journal of Marketing Studies, 2020)
In recent years, there is competition among tourist destinations that has been very drastically. This competition of service quality has forced destinations to restructure to increase their competitive and to attract tourists. Therefore, the study goal is to find out the determinants affecting the satisfaction of foreign tourists in Ho Chi Minh City (HCMC). The researchers surveyed 600 foreign tourists who are visiting HCMC destinations and answered 29 questions but sample size of 565 samples processed. The data collected from June 2019 to December 2019 in HCMC. Simple random sampling technique. Cronbach's Alpha and the exploratory factor analysis (EFA) analyzed and used for Structural Equation Modelling (SEM) technique. Foreign tourists’ responses measured through an adapted questionnaire on a 5-point Likert scale. Finally, the finding of the study has tourism service quality factor which affecting the satisfaction of foreign tourists in HCMC with significance level 0.01.